Chapter 4 Don't be too WEIRD: Research for the Future of Writing Studies - Phelps, Johanna (Taylor & Francis, 2021)
This book invites readers to reconsider how writing studies researchers work with Institutional Review Boards (IRBs) on behalf of their communities and argues that engaging with IRBs during the research design process helps practitioners conduct research more quickly and effectively. Using empirical data from both writing studies and extra-disciplinary contexts, Dr. Johanna Phelps presents findings from two discipline-wide studies, as well as metadata from two IRBs, to develop a principled engagement framework for writing studies researchers to interact with their communities. Phelps further examines the many facets of conducting research with human participants-from comprehending federal policy updates to pondering specific ethical issues to developing detailed research designs-and explores the confluence of ethics, policy, and methodology in a thoroughgoing philosophical investigation of writing studies as a public good. This engaging and timely exploration of research design will be an important resource for scholars and students of writing studies; rhetoric and composition; technical and professional communication; cultural rhetoric; literacy studies; research design; research methodologies; research ethics; IRBs; justice; and critical theory.